A Bi-Categorical Axiomatisation of Concurrent Graph Rewriting - Gadducci, Fabio; Heckel, Reiko; Llabrés, Mercé (Proceedings of the 8th Conference on Category Theory and Computer Science (CTCS 1999), Edinburgh (UK))
In this paper the concurrent semantics of double-pushout (DPO) graph rewriting, which is classically defined in terms of shift-equivalence classes of graph derivations, is axiomatised via the construction of a free monoidal bi-category. In contrast to a previous attempt based on 2-categories, the use of bi-categories allows to define rewriting on concrete graphs. Thus, the problem of composition of isomorphism classes of rewriting sequences is avoided. Moreover, as a first step towards the recovery of the full expressive power of the formalism via a purely algebraic description, the concept of disconnected rules is introduced, i.e., rules whose interface graphs are made of disconnected nodes and edges only. It is proved that, under reasonable assumptions, rewriting via disconnected rules enjoys similar concurrency properties like in the classical approach.

Modeling Agent-Based Systems with Graph Transformation and UML - Heckel, Reiko (Proceedings of the Dagstuhl-Seminar 99451 on Rigorous Analysis and Design for Software Intensive Systems)

Extending UML for Modeling of Multimedia Applications - Sauer, Stefan; Engels, Gregor (Proceedings of the IEEE Symposium on Visual Languages (VL 1999), Tokyo (Japan))
An analysis of how visual modeling of structure and dynamic behavior of a multimedia application differs from modeling conventional software yields that aspects of the graphical user interface and time-dynamic behavior ought to be integral parts of a coherent multimedia application model. In this sense, we extend the model-view-controller paradigm towards multimedia.As a result, we present OMMMA-L, a visual Language for the Object-Oriented Modeling of MultiMedia Applications that is based on the Unified Modeling Language (UML). The structural and behavioral diagram types of UML have been analyzed and are adapted and extended according to multimedia application characteristics.A presentation diagram is introduced and integrated to adequately describe the visual presentation. In addition to explaining the different diagram types, we also give pragmatic guidelines on how to deploy and combine the various diagrams.

Combined Photovoltaic and Solar Thermal Systems for Facade Integration and Building Insulation - Salhi, M. J.; Krauter, Stefan; Lemoine, R.; Triebel, C.; Schroer, S.; Araújo, R. G. (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), .4.–9. Juli 1999, II-88.)

Set-up of a Laboratory for Research and Education in Solar Energy in Rio de Janeiro - Krauter, Stefan; Stephan, R.; Bastos, L. (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), 4.–9. Juli 1999, S. II-288)

Cooling and Less Reflections at Photovoltaic Modules by a Frontside Water Film. - Krauter, Stefan; Schmid, U. (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), 4.–9. Juli 1999)

The Use of Solar Energy: Considerations for Calculations of Greenhouse Gas Reduction by Photovoltaics - Krauter, Stefan (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), 4.–9. Juli 1999, II-375.)

Optical and Thermal Improvements of PV Performance by a Flowing Film of Water at the Frontside of PV Generators. - Krauter, Stefan; Schmid, U. (Proceedings of the 9th Sede Boquer Symposium on Solar Electricity Production, Sede Boquer (Israel), 12.–13. Juli 1999, S. 123–126)

Híbridos Termo/Solares Fotovoltaicos (Combined Solar–Thermal/Photovoltaic Systems) - Krauter, Stefan (Proceedings of Workshop Energias Alternativas para Produção de Calor, Frio e Geração e Conservação de Energia Elétrica, UFSC, Florianópolis, Santa Catarina (Brasilien), 6.–9. Dezember 1999)

Combined PV and Solar Thermal Systems for Facade Integration and Building Insulation - Krauter, Stefan; Araujo, G.; Schroer, S.; Salhi, M.; Triebel, C.; Hanitsch, Rolf (Solar Energy)